LENGTH OF STAY PASIEN NON BEDAH DI INSTALASI GAWAT DARURAT RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2024 - Fitri Muat Ulina Sitepu; Rusmauli Lumban Gaol; Indra Hizkia P (Poltekkes Kemenkes Medan, 2024)
Length of stay in the ER is the patient's waiting time when entering the ER until the patient is directed to go home or transferred to another unit. The patient's length of stay affects treatment and time efficiency. It is not known about the history of patient length of stay in the emergency room. Quantitative observational descriptive research with a cross-sectional approach. The sampling technique uses purposive sampling with sample size of 105 patients, calculated using the Slovin formula. Data analysis uses univariate analysis. The ER assessment time at Elisabeth Hospital Medan has normal time of 92.4% with a target time of ?120 minutes in line with Hani's research in 2022/2023. The review and consultation time for ER patients has a normal time of 91.4% with a target time of ? 60 minutes in line with Hani's research in 2022/2023, the transfer time for non-surgical patients to inpatient care after disposition from the ER has a normal time of 94.3% with a target time of ? 60 minutes in line with Hani's research in 2022/2023, Length of stay for non-surgical patients in The ER has a normal time of 89.5% with a target time of ? 240 in line with Hani's research in 2022/2023. The majority of length of stay for non-surgical patients in the emergency room is in line with the target time. The majority of ED assessment times, reviews and consultations as well as patient transfer times to inpatient care are in accordance with the target time. It is hoped that the results of this research can become reference material and be further developed regarding the number of samples as well as further exploring and adding to other variables studied. Apart from that, add observers to monitor the patient's time in the ER so that there are no difficulties when the ER is overcrowded.